Limnological and Bacteriological Properties of Agba-Ndele Segment of Sombriero River, Rivers State, Nigeria - Otene B. B; Ukwe, I. O. K; Fibika S. C. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
ABSTRACT The quality of our surface waters has deteriorated significantly in many countries in the past few decades due to anthropogenic activities resulting from population growth, urbanization and industrialization. This study was carried out for four Months in Agba-Ndele, Segment of Sombriero River to assess the bacteriological and limnological properties of the water. Water and sediment samples were collected from four sampling stations and analyzed in the laboratory for the bacterial and some other water variables using standard method of APHA. A one-way analysis of variance (ANOVA) was used to ascertain the spatial variation while Duncan Multiple Range Test (DMRT) was used to separate the means where there was significant difference at p<0.05. The results showed that some of the mean values of the water variables studied were, Temperature, 28.44 ± 0.93oC,pH, 6.42 ± 0.65, DO, 6.05 ± 0.37mg/l, Conductivity, 2471.06 ± 569.73us/cm, nitrate, 591.78±41.33 etc some of which were above the permissible limits of WHO, SON, EPA and USEPA guidelines. There were spatial variations with Station 3 significantly different from others while temperature, Dissolved oxygen (DO), conductivity and phosphate exhibited seasonal variations at p<0.05. The mean value of Total Heterotrophic Bacteria in water (THBw) was 5058.13±9286.625 cfu/ml while that of sediment (THBs) was 4132.5±7345.808cfu/g.Total Coliform Bacteria in water (TCBw) was 1743.75 ± 852.423 cfu/ml while that of sediment (TCBs) was 2162.50±709.812 cfu/g with water coliform value lower than the sediment. The bacterial load/count in Station 3 was significantly different from the other stations. Out of the total of 13 bacteria isolated one (1) was absent from the sediment. Agba-Ndele segment of Sombriero river is therefore under threat. Adequate measures should be taken in regulating the level of anthropogenic activities in the area thereby avoiding further deterioration of water.